SURVEY BASED CLASSIFICATION OF BUG TRIAGE APPROACHES - Yadav, Asmita; Singh, Sandeep Kumar (APTIKOM Journal on Computer Science and Information Technologies, 2016)
This paper presents a comprehensive survey of bug triaging approaches in three classes namely machine learning based, meta-data based and profile based. All approaches under three categories are critically compared and some potential future directions and challenges are reported. Findings from the survey show that there is a lot of scope to work in cold-start problem, developer- profiling, load balancing, and reopened bug analysis.